Tofacitinib Treatment of Refractory Cutaneous Leukocytoclastic Vasculitis: A Case Report - Zhu, Kai-Jun; Yang, Pei-Dan; Xu, Qiang (Frontiers in Immunology, 2021)
Introduction: To date, there is no treatment with proven efficacy for cutaneous leukocytoclastic vasculitis (CLV). Several reports have suggested that CLV responds favorably to corticosteroids, colchicine, nonsteroidal anti-inflammatory drugs (NSAIDs), azathioprine, and hydroxychloroquine (HCQ). To the best of our knowledge, the oral small molecule Janus kinase inhibitor, tofacitinib, plays an important role in the treatment of autoimmune and inflammatory diseases. Therefore, tofacitinib may be a prospective therapy in patients with CLV. Case Presentation: A 29-year-old woman presented to our hospital with a 5-year history of symmetric skin lesions mainly affecting both lower extremities. The results for anti-neutrophil cytoplasmic antibodies (ANCA), anti-extracted nuclear antigens (ENA) autoantibodies, anti-double-stranded deoxyribonucleic acid (dsDNA) antibodies, and antinuclear antibodies (ANA) were all negative. The definite diagnosis of CLV was determined by a skin biopsy. However, the patient exhibited a poor response to prednisone, HCQ, methotrexate, colchicine, azathioprine, and tripterygium wilfordii polyglycoside tablets (TGTs) treatments. She was then treated with oral tofacitinib (5 mg twice daily) and oral prednisone (25 mg daily). Outcomes: Her skin lesions gradually improved over a period of 4 weeks. Two months later, the skin ulcers completely resolved. No evidence of recurrence of skin ulcers was observed during a 6-month follow-up. Conclusion: We present the first case of a female patient receiving short-term tofacitinib therapy for refractory CLV. Tofacitinib may be a promising oral alternative for patients with CLV. However, its efficacy and safety require further appraisal through clinical trials.